Genetic, clinic and histopathologic characterization of BRCA-associated hereditary breast and ovarian cancer in southwestern Finland - Pallonen Terhi Aino-Sofia; Lempiäinen Salla Maria Matleena; Joutsiniemi Titta Kristiina; Aaltonen Riitta Irmeli; Pohjola Pia Erika; Kankuri-Tammilehto Minna Kristiina (NATURE PORTFOLIO, 2022)
We have analyzed the histopathological, clinical, and genetic characteristics in hereditary breast and ovarian cancer patients of counselled families from 1996 up to today in the southwestern Finland population. In this study we analyzed the incidence of different BRCA1 and BRCA2 pathogenic variants (PV). 1211 families were evaluated, and the families were classified as 38 BRCA1 families, 48 BRCA2 families, 689 non-BRCA families and 436 other counselled families (criteria for genetic testing was not met). In those families, the study consisted of 44 BRCA1 breast and/or ovarian cancer patients, 58 BRCA2 cancer patients, 602 non-BRCA patients and 328 other counselled patients. Breast cancer mean onset was 4.6 years earlier in BRCA1 carriers compared to BRCA2 (p = 0.07, a trend) and ovarian cancer onset almost 11 years earlier in BRCA1 families (p < 0.05). In BRCA families the onset of ovarian cancer was later than 40 years, and BRCA2-origin breast cancer was seen as late as 78 years. The BRCA PV (9%) increases the risk for same patient having both ovarian and breast cancer with a twofold risk when compared to non-BRCA group (4%) (95% CI p < 0.05). Triple-negativity in BRCA1 (42%) carriers is approximately 2.6 times vs more common than in BRCA2 carriers (16%) (p < 0.05). The risk ratio for bilateral breast cancer is approximately four times when compared BRCA2 (17%) and other counselled patients' group (4%) (p < 0.05). 27% southwestern BRCA2-families have a unique PV, and correspondingly 39% of BRCA1-families. The results of this analysis allow improved prediction of cancer risk in high-risk hereditary breast and ovarian families in southwestern Finland and improve long term follow-up programs. According to the result it could be justified to have the discussion about prophylactic salpingo-oophorectomy by the age of 40 years. The possibility of late breast cancer onset in BRCA2 carriers supports the lifelong follow-up in BRCA carriers. Cancer onset is similar between BRCA2 carries and non-BRCA high-risk families. This study evaluated mutation profile of BRCA in southwestern Finland. In this study genotype-phenotype correlation was not found